Biot‐type scattering effects in gas hydrate‐bearing sediments - Rubino, Jorge Germán (2008)
This paper studies the energy conversions that take place at discontinuities within gas hydrate-bearing sediments and their influence on the attenuation of waves traveling through these media. The analysis is based on a theory recently developed by some of the authors, to describe wave propagation in multiphasic porous media composed of two solids saturated by a single-phase fluid. Real data from the Mallik 5L-38 Gas Hydrate Research well are used to calibrate the physical model, allowing to obtain information about the characteristics of the cementation between the mineral grains and gas hydrates for this well. Numerical experiments show that, besides energy conversions to reflected and transmitted classical waves, significant fractions of the energy of propagating waves may be converted into slow-waves energy at plane heterogeneities within hydrated sediments. Moreover, numerical simulations of wave propagation show that very high levels of attenuation can take place in the presence of heterogeneous media composed of zones with low and high gas hydrate saturations with sizes smaller or on the order of the wavelengths of the fast waves at sonic frequencies. These attenuation levels are in very good agreement with those measured at the Mallik 5L-38 Gas Hydrate Research Well, suggesting that these scattering-type effects may be a key-parameter to understand the high sonic attenuation observed at gas hydrate-bearing sediments.